2015
DOI: 10.1159/000441977
|View full text |Cite
|
Sign up to set email alerts
|

Complete Idiopathic Hypogonadotropic Hypogonadism due to Homozygous <b><i>GNRH1</i></b> Mutations in the Mutational Hot Spots in the Region Encoding the Decapeptide

Abstract: Introduction: Mutations of the human GNRH1 gene are an extremely rare cause of normosmic idiopathic hypogonadotropic hypogonadism (nIHH), with only 6 mutations so far described. Patients: As part of a larger study, families with IHH were screened for mutations in genes known to be associated with IHH. In family 1, a 15-year and 9-month-old boy first presented during infancy with micropenis and bilateral cryptorchidism. His pubic and axillary hair is at stage 4 and 2, respectively. His testes are 1 ml bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
17
0
3
Order By: Relevance
“…Out of 310 patients with IHH, only one case was found, attesting to the rarity of mutations in this gene as a cause of IHH ( 70 ). We recently reported further GNRH1 mutations located in the region encoding the decapeptide which is the same region involved in earlier reported mutations ( 71 ).…”
Section: Introductionsupporting
confidence: 65%
“…Out of 310 patients with IHH, only one case was found, attesting to the rarity of mutations in this gene as a cause of IHH ( 70 ). We recently reported further GNRH1 mutations located in the region encoding the decapeptide which is the same region involved in earlier reported mutations ( 71 ).…”
Section: Introductionsupporting
confidence: 65%
“…GNRH1 has been considered for several years an obvious candidate for mutations in patients with nCHH, but so far only three different homozygous mutations have been described (Fig. 3C) (42,43,44). In our study, we identified a novel GNRH1 homozygous mutation located at the consensus splicing site region upstream the start of exon 2 (c.142-2A>C).…”
Section: Discussionmentioning
confidence: 67%
“…GNRH1, KISS1, TAC3) of the above-mentioned receptors are far more rare. Indeed, only 4 nCHH families carrying biallelic GNRH1 mutations have been reported (50)(51)(52), along with a few cases of nCHH/KS probands with monoallelic mutations and an additional mutation in another CHH/KS loci (i.e. potential oligogenic transmission -see below) (51,53,54).…”
Section: Chh/ks Is a Treatable Form Of Infertilitymentioning
confidence: 99%